PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN MINYAK JELANTAH MENJADI LILIN AROMA TERAPI (JELILIN) UNTUK MENDUKUNG EKONOMI KREATIF DAN PENGELOLAAN LIMBAH RAMAH LINGKUNGAN - Fahru Rozi; Endang Puspitasari; Muhammad Zainul Mustofa; Mahshunatin Amaliya (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service project aims to provide education and practical skills for local residents to recycle used cooking oil into eco-friendly and economically valuable aroma therapy candles, named JELILIN. The target partners are community members actively involved in training sessions. The implementation strategy includes awareness sessions on the negative impacts of used oil, hands-on demonstrations of JELILIN production, and mentoring in product development and marketing. The results indicate an 85% increase in community knowledge of waste management and a 90% improvement in candle-making skills based on pre- and post-training evaluations. JELILIN not only helps reduce environmental pollution but also fosters creative business opportunities, thereby strengthening community empowerment and contributing to sustainable environmental conservation.